(untitled) (Journal of Fiber Bioengineering and Informatics, 2018)
Optimization of cured cotton textiles through self-cleaning property constructs the main goal of present investigation. Cotton textiles with 0.1, 0.3, 0.5, 1 and 1.5 wt% were cured by Nano-titanium dioxide (P25 Degussa) with and without using cross-link method. Stability of the TiO_2 coatings is a particular requirement for textiles because they are subject to frequent washing hence use of a suitable coating condition is necessary. During this study sucsinic acid was used as spacers to attach TiO_2 to cotton. Viscosity degree of titania particles to cotton fabrics is studied by burning method by determining the percentage of titania coated. Further, following experiments were conducted: thermal behaviour of curing samples with TGA, self-cleaning degree of curing cotton fabrics and stained samples with Dark green BN green 6 and Reactive orange V-2G dyes under irradiation of 20 & 400 W UV lamps using reflectance spectrophotometer, structure and morphology of titania coated cotton fabric through scanning electron microscopy (SEM) and crystallinity of titania coatings by X-ray diffraction (XRD). Tearing strength of cured cotton fabrics was investigated before and after employing irradiation process. Results show that stability of Nano TiO_2 coating and degree of self-cleaning cured with cross-link method is extremely higher than in non cross-link operation and cotton cellulosic chains are not decomposed by photocatalytic activity of titania.